Trans-Spinal Focused Ultrasound Stimulation Selectively Modulates Descending Motor Pathway - Evgenii Kim; Jeungeun Kum; Hyungmin Kim (IEEE Transactions on Neural Systems and Rehabilitation Engineering, 2022)
Compared to current non-invasive methods utilizing magnetic and electrical means, focused ultrasound provides greater spatial resolution and penetration depth. Despite the broad application of ultrasound stimulation, there is a lack of studies dedicated to the investigation of acoustic neuromodulation on the spinal cord. This study aims to apply focused ultrasound on the spinal cord to modulate the descending pathways in a non-invasive fashion. The application of trans-spinal focused ultrasound (tsFUS) was examined on the motor deficit mouse model. tsFUS was achieved using a single-element focused ultrasound transducer operating at 3 MHz. The sonication was performed on anesthetized 6 week-old mice targeting T12 and L3 vertebrae. The effect was analyzed by comparing electromyography responses from the hindlimb induced by electrical stimulation of the motor cortex. Further, the mouse model with the Harmaline-induced essential tremor (ET) was selected to investigate the potential clinical application of tsFUS. The safety was verified by histological assessment. Sonication at the T12 area inhibited motor response, while sonication over the L3 region provided signal enhancement. Sonication of T12 of the ET mouse also showed the ability of ultrasound to suppress tremors. Meanwhile, the histological examination did not show any abnormalities with the highest applied acoustic pressure. In this work, a non-invasive motor signal modulation was achieved using tsFUS. Moreover, the results showed the ability of focused ultrasound to manage tremors in a safe manner. This study provides a stepping stone for the trans-spinal application of focused ultrasound to motor-related disorders.